Urine Assay to Measure Tenofovir Concentrations in Patients Taking Tenofovir Alafenamide - Lalley-Chareczko, Linden; Hiserodt, Emily; Moorthy, Ganesh; Zuppa, Athena; Mounzer, Karam; Koenig, Helen (Frontiers in Pharmacology, 2020)
HIV pre-exposure prophylaxis(PrEP) with tenofovir/emtricitabine is effective when taken daily. Previously, we developed a urine assay capable of detecting the prodrug tenofovir(TFV) in patients taking tenofovir disoproxil fumarate(TDF)-based PrEP. However, tenofovir alefenamide(TAF) has replaced TDF as a less toxic tenofovir formulation for HIV treatment and is under study as PrEP. Given the need to ensure the aforementioned assay remains available for the purpose of therapeutic drug monitoring, it is critical to ensure its accuracy for detecting TFV in patients taking TAF. Blood and urine samples were collected from 3 cohorts of patients: 1)10 HIV+ participants with suppressed virus on a TAF-based regimen, 2)10 HIV- participants administered 1 dose of TAF/FTC followed by urine and plasma sampling for 7 days starting 1-3 hours post-dose, and 3)10 HIV- participants administered 7 doses of TAF/FTC followed by urine and plasma sampling for 10 days starting 1-3 hours after the last dose. Samples were analyzed using liquid chromatography-tandem mass spectrometry(LC-MS/MS) with high sensitivity and specificity for TFV. HIV- samples from were compared to a historical cohort administered one dose of TDF/FTC. HIV+ participants were 90% male, 40% African American, and 10% Hispanic(mean age=57y;SD 8.88y). HIV- participants were 55% male and 70% Caucasian(mean age=31.6y;SD 7.70y). HIV+ samples demonstrated TFV concentrations 2 logs higher in urine than plasma(1000ng/mL versus +/-10ng/mL). Urine samples following a single dose of TAF in HIV- subjects yielded TFV concentrations ranging from 100-1000ng/mL 1-3 hours post-dose and remained >100ng/mL for 6 days in 8 of 10 participants. Urine samples collected after 7 consecutive doses of TAF yielded TFV concentrations >1000ng/mL 1-3 hours after dosing discontinuation, with TFV concentrations >100ng/mL 7 days post discontinuation in 8 of 10 participants. Urine TFV concentrations following TAF administration were comparable to those from a historical cohort administered TDF/FTC. Plasma TFV concentrations were low(+/-10ng/mL) in both HIV- cohorts at all time points. TFV persists in urine at detectable concentrations in patients taking TAF/FTC for at least 7 days despite largely undetectable plasma levels, with urine TFV concentrations comparable to patients taking TDF/FTC. This study demonstrates the feasibility of using a urine TFV assay for TAF adherence.